Performance of coagulation tests in patients on therapeutic doses of rivaroxaban - Francart, Suzanne J.; Hawes, Emily M.; Deal, Allison M.; Adcock, Dorothy M.; Gosselin, Robert; Jeanneret, Cheryl; Friedman, Kenneth D.; Moll, Stephan (Thrombosis and Haemostasis, 2014)
Knowledge of anticoagulation status during rivaroxaban therapy is desirable in certain clinical situations. It was the study objective to determine coagulation tests most useful for assessing rivaroxaban’s anticoagulant effect. Peak and trough blood samples from 29 patients taking rivaroxaban 20 mg daily were collected. Mass spectrometry and various coagulation assays were performed. “On-therapy range” was defined as the rivaroxaban concentrations determined by LC-MS/ MS. A “misprediction percentage” was calculated based on how often results of each coagulation assay were in the normal reference range, while the rivaroxaban concentration was in the “on-therapy” range. The on-therapy range was 8.9 – 660 ng/ml. The misprediction percentages for prothrombin time (PT) and activated partial thromboplastin time (aPTT), using multiple reagents and coagulometers, ranged from 10% – 52% and 31% – 59%, respectively. PT, aPTT and activated clotting time (ACT) were insensitive to trough rivaroxaban: 59%, 62%, and 80% of samples had a normal result, respectively. Over 95% of PT and ACT values were elevated at peak. Four different rivaroxaban calibrated anti-Xa assays had R2 values >0.98, demonstrating strong correlations with rivaroxaban drug levels. In conclusion, PT, aPTT and ACT are often normal in patients on therapeutic doses of rivaroxaban. However, PT and ACT may have clinical utility at higher drug plasma levels. Rivaroxaban calibrated anti-factor Xa assays can accurately identify low and high on-therapy rivaroxaban drug levels and, therefore, have superior utility in all clinical situations where assessment of anticoagulation status may be beneficial.This trial is registered at www.clinicaltrials.gov (#NCT01743898).
Keywords: Clinical trials; oral anticoagulants; pharmacodynamics; thrombosis